Growth and performance of maize treated with different types of biochar grown in lateritic soil / Siti Hajar Said - Said, Siti Hajar (Faculty of Plantation and Agrotechnology, 2014)
This study was conducted to investigate the effect of biochar on the growth performance of maize grown on lateritic soil. This experiment was conducted at Universiti Technologi MARA, Perlis. The twelve treatments inclusive of control treatment were used Cattle dung biochar (CDB), Chicken manure biochar (CMB), Rice husk biochar (RHS) and Coconut shell biochar (CSB) at rate 10, 20 and 40 ton/ha. The experiment design was completely randomize design (CRD) with 3 replications. The biochar treatment was applied a week before planting. Plant height, plant girth leaf area meter and number of leaf were recorded at the 2nd, 4th, 6th, and 8th week after planting. After 8th week of planting the plants were harvested. The nutrient content in leaf and soil were determined by standard procedures. It was found that, the cattle dung biochar (CDB) showed the positive result in plant height and girth. Beside that the soil pH were increase by applying chicken manure biochar (CMB) at rate 40 ton/ha. Therefore it might be recommended to use biochar as an alternative fertilizer to improve plant growth and soil properties also act as liming to increase the soil pH.